2010
DOI: 10.1270/jsbbs.60.568
|View full text |Cite
|
Sign up to set email alerts
|

Gene-gene interactions between mutants that accumulate abnormally high amounts of proglutelin in rice seed

Abstract: We had previously identified eight mutants, esp2 and g(G)lups1 to 7, which accumulated abnormally high amounts of proglutelin, the major storage protein in rice seeds. Analysis of their seed proteins by SDS-PAGE, their levels of the luminal chaperone BiP and gene-gene interactions indicated that these mutants fell into four classes. The most epistatic class consisted of esp2, which encodes a defective protein disulfide isomerase (PDI). A second class consisting of Glup1, glup2 and glup7 was hypostatic to esp2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 32 publications
3
33
0
1
Order By: Relevance
“…Previous studies have identified eight 57H mutants in rice, including esp2 and glup1 to glup7 (Ueda et al, 2010). Compared with these previously reported rice 57H mutants, the gpa3 mutant displayed several distinct features.…”
Section: Discussion Gpa3 Is Defective In Post-golgi Trafficking Of Stmentioning
confidence: 86%
See 3 more Smart Citations
“…Previous studies have identified eight 57H mutants in rice, including esp2 and glup1 to glup7 (Ueda et al, 2010). Compared with these previously reported rice 57H mutants, the gpa3 mutant displayed several distinct features.…”
Section: Discussion Gpa3 Is Defective In Post-golgi Trafficking Of Stmentioning
confidence: 86%
“…Compared with these previously reported rice 57H mutants, the gpa3 mutant displayed several distinct features. First, gpa3 accumulated normal levels of PDI1-1 and BiP1, whereas those mutants that have defects in ER export of storage proteins usually exhibited elevated levels of these chaperones, such as esp2/pdi1-1 (Takemoto et al, 2002), glup1, glup2, and glup7 (Ueda et al, 2010). Second, despite the fact that these mutants all accumulate increased levels of proglutelins, there are distinct differences in their subcellular characteristics due to lesions in different trafficking processes.…”
Section: Discussion Gpa3 Is Defective In Post-golgi Trafficking Of Stmentioning
confidence: 99%
See 2 more Smart Citations
“…The mutants were named endosperm storage protein mutant2 (esp2; Kumamaru et al, 1987Kumamaru et al, , 1988 and glutelin precursor mutant1 (glup1) to glup7 (Kumamaru et al, 2007;Satoh-Cruz et al, 2010a;Ueda et al, 2010). Gene-gene interaction analyses of the eight mutant lines indicate that esp2 is the most epistatic while glup3 is the most hypostatic among the eight mutant genes (Ueda et al, 2010). This relationship suggests that the factors encoded by ESP2 and GLUP3 function upstream and downstream, respectively, of the other GLUP genes in the pathway of the synthesis, trafficking, and accumulation of proglutelin.…”
mentioning
confidence: 99%